EKONOMI RUMAH TANGGA DI ERA PANDEMI COVID-19 - Peter Garlans Sina (Universitas Nusa Cendana, 2020)
Covid-19 Pandemic which occurred in early 2020 has resulted in economic decline in Indonesia and the government also urges the public for a health protocol. The after effect is that MSMEs go bankrupt and there is a work termination so that more and more household economies experience life difficulties. There have been some assistances provided by the Government, but they have not been maximally increased the household economy until the new normal era. However, this condition must still be carried out in a management of all household resources which one of them is household finance and also the improvement of new skills. Keywords : Household Economic, Health Protocol, Covid-19